Nanoporous Gold Electrodes and Their Applications in Analytical Chemistry. (20th February 2013) - Collinson, Maryanne M.
Abstract : Nanoporous gold prepared by dealloying Au:Ag alloys has recently become an attractive material in the field of analytical chemistry. This conductive material has an open, 3D porous framework consisting of nanosized pores and ligaments with surface areas that are 10s to 100s of times larger than planar gold of an equivalent geometric area. The high surface area coupled with an open pore network makes nanoporous gold an ideal support for the development of chemical sensors. Important attributes include conductivity, high surface area, ease of preparation and modification, tunable pore size, and a bicontinuous open pore network. In this paper, the fabrication, characterization, and applications of nanoporous gold in chemical sensing are reviewed specifically as they relate to the development of immunosensors, enzyme-based biosensors, DNA sensors, Raman sensors, and small molecule sensors.